2019
DOI: 10.1038/s41598-019-49107-y
|View full text |Cite
|
Sign up to set email alerts
|

Triboelectrification of Two-Dimensional Chemical Vapor Deposited WS2 at Nanoscale

Abstract: Triboelectric properties of chemical vapor deposited WS 2 nanoflakes have been characterized in nano-range by atomic force microscopy (AFM) and Kelvin force microscopy (KFM). The triboelectric process is dependent on the thickness of WS 2 nanoflakes, and it is sensitive to the adsorbates like water molecules, as well as transferred Pt from the tip on the sample. The density of tribo-charge can be modified by applying various biases to the conductive Pt-coated tip d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…[1056] Wang et al confirmed the WS 2 's triboelectric property using Kelvin force microscopy (KFM). [1057] WS 2 -based TENG was recently fabricated by Kim et al with surface modification of thiolated ligands to enhance the TENG performance (Figure 9c). [1058] Thiolated ligands acted as a p-type dopant for WS 2 , increasing the potential difference between the two triboelectric electrodes, resulting in a 10-fold increase in TENG performance compared to TENG using pure WS 2 .…”
Section: Performance Of 2d Materials-based Triboelectric Nanogeneratormentioning
confidence: 99%
See 1 more Smart Citation
“…[1056] Wang et al confirmed the WS 2 's triboelectric property using Kelvin force microscopy (KFM). [1057] WS 2 -based TENG was recently fabricated by Kim et al with surface modification of thiolated ligands to enhance the TENG performance (Figure 9c). [1058] Thiolated ligands acted as a p-type dopant for WS 2 , increasing the potential difference between the two triboelectric electrodes, resulting in a 10-fold increase in TENG performance compared to TENG using pure WS 2 .…”
Section: Performance Of 2d Materials-based Triboelectric Nanogeneratormentioning
confidence: 99%
“…confirmed the WS 2 's triboelectric property using Kelvin force microscopy (KFM). [ 1057 ] WS 2 ‐based TENG was recently fabricated by Kim et al. with surface modification of thiolated ligands to enhance the TENG performance (Figure 9c).…”
Section: D Materials Based Wearable Energy Harvesting Technologiesmentioning
confidence: 99%
“…These TTE charges can therefore modulate the electronic properties of CVD SLG, leading to n-doped or p-doped SLG, depending on the type of TTE charge. In addition, the TTE effects have also been demonstrated on silica-supported MoS 2 , and WS 2 . However, none of the aforementioned studies on the SLG surfaces have discussed the WF of SLG after being rubbed by an electrically biased cAFM probe.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the TTE effects have also been demonstrated on silicasupported MoS 2 40,41 and WS 2 . 42 However, none of the aforementioned studies on the SLG surfaces have discussed the WF of SLG after being rubbed by an electrically biased cAFM probe. To fully exploit SLG in device application, the manner in which various experimental conditions, such as the relative humidity (RH) and polarity and magnitude of the applied electric bias, may influence the WF of SLG must be examined in detail.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most important scientific discoveries of the early 21 st century is the successful production of graphene, a two-dimensional carbon crystal with a hexagonal lattice (Geim, Novoselov 2010). This fact, as well as the unique properties of graphene, gave rise to works on the synthesis, analysis and modelling of new two-dimensional materials with desired properties, see, for example, recent publications in Nature Communications (Tang et al 2019) and Scientific Reports (Bravo et al 2019;Wang et al 2019). Graphene has high strength and plasticity (Frank et al 2007;Lee et al 2008), special electronic properties due to the presence of a Dirac cone in its band structure (Avouris 2010;Castro Neto et al 2009), and a record high thermal conductivity (Balandin et al 2008).…”
Section: Introductionmentioning
confidence: 99%